If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(4xy + -10) + 3(3xy + 6) = 0 Reorder the terms: -1(-10 + 4xy) + 3(3xy + 6) = 0 (-10 * -1 + 4xy * -1) + 3(3xy + 6) = 0 (10 + -4xy) + 3(3xy + 6) = 0 Reorder the terms: 10 + -4xy + 3(6 + 3xy) = 0 10 + -4xy + (6 * 3 + 3xy * 3) = 0 10 + -4xy + (18 + 9xy) = 0 Reorder the terms: 10 + 18 + -4xy + 9xy = 0 Combine like terms: 10 + 18 = 28 28 + -4xy + 9xy = 0 Combine like terms: -4xy + 9xy = 5xy 28 + 5xy = 0 Solving 28 + 5xy = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-28' to each side of the equation. 28 + -28 + 5xy = 0 + -28 Combine like terms: 28 + -28 = 0 0 + 5xy = 0 + -28 5xy = 0 + -28 Combine like terms: 0 + -28 = -28 5xy = -28 Divide each side by '5y'. x = -5.6y-1 Simplifying x = -5.6y-1
| 6+4r=5r | | 3-3*6-2=12 | | 18-r=-323 | | -15x-14= | | 4x-1=10x+8 | | 22+z=-180 | | Y=x+-5 | | 249=4x^2+32x-11 | | 8-d=d-6 | | 7+5j=6j | | Ax-y+z=6 | | -0.03x+0.11(x+16000)=2080 | | 5t+7r-15r= | | 3t-8=-2t+7 | | 18=3(v-13)-6 | | 5x+19+7x+98=213 | | 3t-8=-2the+7 | | 3t-8=-3 | | 5+4x=-1x | | 9h=-8+10h | | 8x-4=y | | 3(x+2)+23= | | 3x+7x-5x= | | 2(y-3)+5=3(x-1) | | 6(-5x+1)=-204 | | 0=1.5x-3.4 | | 2(710+1)= | | 3(-8+8x)=-192 | | (x-2)(x^2-2x+4)-x(x-3)(x+3)=26 | | 5q+-6q-p= | | 1410+2= | | 5(2t+3)=30-5t |